The First Manned Moon Landing as Takeoff for Global History: An Overview - Grampp, Sven (Springer Fachmedien Wiesbaden, 2024)
The media coverage of the first manned moon landing serves as a starting point for the discussion of possibilities, limitations, and different designs of a global history. This introduction presents four different approaches to global history, namely global history (1) as communication-technological globalization, (2) as a transnational and transcontinental operation of addition, (3) as a comparative procedure, and (4) as reflexive glocalization. These four approaches will be aligned with the perspectives developed by the different contributions in this volume. Thus, the introduction also elaborates en passant what the reader can (and also should not) expect to find in this essay collection.
CRIS-Team Scopus Importer:2025-10-16